2013
DOI: 10.1007/s12022-013-9234-2
|View full text |Cite
|
Sign up to set email alerts
|

Dermoid Cyst of the Lateral Neck Associated with the Thyroid Gland: a Case Report and Review of the Literature

Abstract: Dermoid cysts are the most common teratomatous lesion; however, they infrequently arise in the head and neck region. Very rarely, dermoid cysts have been described in the thyrohyoid region, masquerading as a thyroid nodule. We describe the case of a 31-year-old woman with a lateral neck mass, associated with the thyroid gland inferiorly, which was excised and found to be a dermoid cyst. We then review the pathogenesis of dermoid cysts in this region, as well as review diagnosis and treatment of dermoid cysts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Typically, dermoid cysts are asymptomatic but can cause complications such as inflammation, dysphagia, dystonia, disorders of swallowing, chewing, or vocal function, and airway encroachment due to mass effects (15,16). Those complications are mostly related to cyst size.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, dermoid cysts are asymptomatic but can cause complications such as inflammation, dysphagia, dystonia, disorders of swallowing, chewing, or vocal function, and airway encroachment due to mass effects (15,16). Those complications are mostly related to cyst size.…”
Section: Discussionmentioning
confidence: 99%
“…The teratoid cyst is also an epithelium-lined cyst containing mesodermal or endodermal elements, such as the muscle, bone, teeth and mucous membranes [ 1 , 2 ]. Dermoid cysts, which are congenital, are caused by the entrapment of ectodermal tissues during midline closure of the first and second branchial arches [ 5 ] and the abnormal burial of a lateral cervical cyst or the residual tuberculum impar [ 6 ]. Moreover, they can be attributed to the entrapment of epithelial debris due to trauma, inflammation or surgery and epidermal atheromas [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, imaging alone may not be able to distinguish between lesions. For example, radiologically it is very difficult to differentiate between a dermoid cyst confined within the sublingual space, and a ranula 8 9. This is evidenced by Puricelli et al , who reported the recurrence of a dermoid cyst treated two times by marsupialisation as it was misdiagnosed previously for a ranula.…”
Section: Discussionmentioning
confidence: 99%